PENGARUH OVERHEAD COST, RISK COST, DAN SIMPANAN WADIAH TERHADAP PENDAPATAN MARGIN MURABAHAH PADA BANK UMUM SYARIAH - Danu Satria; Sugianto Sugianto; Rahmat Daim (LP2M Universitas Bina Bangsa, 2024)
This research aims to determine whether there is an influence of Overhead Costs, Risk Cost and Wadiah Savings on Murabahah Margin Income at Sharia Commercial Banks. The dependent variable applied in this research is Murabahah Margin Income, the independent variables applied in this research are Overhead Cost, Risk Cost and Wadiah Savings. This research took a sample of eight Islamic commercial banks in Indonesia within the research time period starting from the 2018-2022 period. The data in this research uses secondary data which is processed using the Eviews 10 program. This research uses panel data regression analysis with the Fixed Effect Model (FEM) approach. Based on the results of hypothesis testing, it can be concluded that partially the Overhead Cost variable has no influence on murabahah margin income. Partially Risk Cost has a significant influence on murabahah margin income and partially Wadiah Savings has a significant influence on murabahah margin income. The research results show that simultaneously or together the overhead cost, risk cost and wadiah savings variables have an influence on murabahah margin income